2022
DOI: 10.1039/d2ra02141b
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical hollow-tubular porous carbon microtubes prepared via a mild method for supercapacitor electrode materials with high volumetric capacitance

Abstract: In this paper, hollow-tubular porous carbons were synthesized from abundant biomass Cycas fluff (CF) through simple carbonization followed by an NaHCO3 mild activation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 63 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…36 These weak and broad peaks indicated that all samples were composed of graphitized carbon atoms and mixed-layer stacking with a well-developed pore structure, but the carbon material exhibited a relatively poorly crystalline structure. 37 The broad peaks reflected by the (002) and (100) crystalline surfaces exhibited graphitic carbon and interlayer condensation, respectively, and no additional peaks were found in all samples; thus, the materials were completely carbonized, and no other impurities were introduced. 38 In addition, HPBC-750-4 showed a distinct high-intensity peak in the small-angle region (2 θ < 20°), which indicated the presence of high-density micropores, consistent with the results of SEM and N 2 adsorption–desorption isotherm analysis.…”
Section: Resultsmentioning
confidence: 85%
“…36 These weak and broad peaks indicated that all samples were composed of graphitized carbon atoms and mixed-layer stacking with a well-developed pore structure, but the carbon material exhibited a relatively poorly crystalline structure. 37 The broad peaks reflected by the (002) and (100) crystalline surfaces exhibited graphitic carbon and interlayer condensation, respectively, and no additional peaks were found in all samples; thus, the materials were completely carbonized, and no other impurities were introduced. 38 In addition, HPBC-750-4 showed a distinct high-intensity peak in the small-angle region (2 θ < 20°), which indicated the presence of high-density micropores, consistent with the results of SEM and N 2 adsorption–desorption isotherm analysis.…”
Section: Resultsmentioning
confidence: 85%
“…The C 1s spectra showcase three prominent peaks located at approximately 284.8, 285.7, and 286.8 eV in Figure a, which can be assigned to the C–C/CC, C–N, and C–OH bonds, respectively. , The N 1s spectra for all samples (Figure b) can be divided into two peaks characterized by the presence of pyridinic-N (398.2–398.5 eV, N-6) and pyrrolic-N (400.4–1.6 eV, N-5). , Previous studies have reported that the presence of N-5 and N-6 can induce the carbon structure surface polarization, resulting in improved pseudocapacitance of carbon materials . Additionally, the high-resolution O 1s spectroscopy of NC, NPC-Z and NPC-CZ samples illustrated two peaks at about 531.6 and 533.6 eV in Figure c, referring to C = O and C–OH groups, respectively. , Oxygen-containing functional groups contribute to improving the ability of wettability as well as charge storage capacity while reducing transfer resistance for carbon materials, especially the C–OH hydroxyl group. To summarize, the high nitrogen and oxygen atomic percentage present in NC, NPC-Z and NPC-CZ samples prove beneficial toward improving surface wettability and providing partial pseudocapacitance, the increase in the atomic percentage of O element from 14.96% to 16.97% (Table ) during activation procedure indicates the formation of oxygen-containing groups. , …”
Section: Resultsmentioning
confidence: 97%
“…It can be seen from Figure 7 a–c, the as-prepared carbon material possessed a large specific surface area (1891.9 m 2 /g) and high microporosity (82.3%) at 800 °C, which is 169 and 12.8 times that of untreated corn straw, respectively. Xiao et al [ 85 ] developed hollow-tubular porous carbon by using biomass Cycas fluff (CF) through carbonization and NaHCO 3 activation at different temperatures. As shown in the Figure 7 d-f, under the pyrolysis temperature of 700 °C, porous carbon had a specific surface area of 397.92 m 2 /g and the microporosity of 73.91% at the mass ratio of 1:2 (CF:NaHCO 3 ).…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%
“… ( a – c ) Impact of temperature on NaHCO 3 activation effect [ 84 ]; ( d – f ) Impact of char/alkali mass ratio on NaHCO 3 activation effect [ 85 ]. …”
Section: Figurementioning
confidence: 99%